PENGARUH KEBISINGAN DAN KELELAHAN TERHADAP TEKANAN DARAH DI PABRIK ROTAN - Galih Adjie Pangestu (Bajang Institute, 2024)
Blood pressure is an important factor in the human body's circulatory system. Blood pressure is always needed to drive blood flow in the arteries, arterioles, capillaries, and venous systems to produce stable blood flow. If blood circulation becomes insufficient, the transport system for oxygen, carbon dioxide and other waste products is disrupted. This study aims to determine the effect of noise and fatigue on blood pressure in a rattan factory. This research uses an analytical observational research design with a cross sectional approach. The population in this study were all employees who worked at the Majaro Rattan Factory with a total of 50 employees. The sample in this study was 50 employees who were selected using the total sampling method. The research instruments used to collect data were a tentimeter used to measure blood pressure, a Sound Level Meter used for noise and a Questionnaire for measuring feelings of work fatigue (KAUPK2) used to measure workers' fatigue. Data analysis techniques in this research include univariate analysis, bivariate analysis and multivariate tests. The results of this study found that 1) There is a significant relationship between noise and blood pressure of workers at the Majaro Rattan Factory, Jepara Regency with a p-value of 0.000 (P<0.05). 2) There is no relationship between fatigue and blood pressure of workers at the Majaro Rattan Factory, Jepara Regency with a p-value of 0.063 (P>0.05). 3) Multivariately, a significant relationship was found between noise and workers' blood pressure at the Majaro Rattan Factory, Jepara Regency with a p-value of 0.013 (P<0.05). Meanwhile, for the fatigue variable, no significant relationship was found with a p-value of 0.335 (P>0.05).